Recent Advances in the Indonesian Paediatric Gastroenterology - Suharjono Suharjono; Sunoto Sunoto; Aswitha Budiarso; W.A.F.J. Tumbelaka; Michael Gracey (Indonesian Pediatric Society, 1978)
Recent advances in the Indonesian Paediatric Gastroenterology have been presented in the 4 following headings and conclusions :(1)'ROSE' system as the principle of treatment of diarrhoea, which is proven to be effective and gives an excellent result in reducing the case fatality rate of acute gastroenteritis, especially cholera.(2) MCT and low lactose containing formula in low birth weight infants gives good to excellent results in improving fat malabsoprtion, ceasing the diarrhoea and increase of body weight.(3 The preliminary study in malnourished Indonesian children has shown that the paediatric enterotest duodenal capsule can be used to study the upper intestinal microflora. It is useful in studying the human intestinal microflora in places where radiologic examination is not available and can easily be used in field studies.(4) The presesent report is the first study to document duovirus shown electron microscopically as virus particles in faecal specimens from children in Indonesia where malnutrition and diarrhoea remain important problems.